2001
DOI: 10.1021/jp0101561
|View full text |Cite
|
Sign up to set email alerts
|

Lattice Model Studies of Force-Induced Unfolding of Proteins

Abstract: We probe the general characteristics of force-induced unfolding of proteins using lattice models. The computations show that the experimental observations, such as the shape of the force-extension curves and hysteresis, are qualitatively reproduced using the coarse-grained models. Force hysteresis, which occurs because the structural relaxation times are longer than the time scales for dissipation of stored mechanical energy, strongly depends on the rate of application of force or the pulling speed. As a resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 22 publications
3
32
0
Order By: Relevance
“…In the presence of a constant f and assuming a rapid alignment of the end-to-end vector ជ R along the force direction, the total energy of the polypeptide is E f ϭ E Ϫ fR. We calculated f-dependent thermodynamic quantities by using a version of the multiple histogram method, in which both temperature T and f are varied (18).…”
Section: Methodsmentioning
confidence: 99%
“…In the presence of a constant f and assuming a rapid alignment of the end-to-end vector ជ R along the force direction, the total energy of the polypeptide is E f ϭ E Ϫ fR. We calculated f-dependent thermodynamic quantities by using a version of the multiple histogram method, in which both temperature T and f are varied (18).…”
Section: Methodsmentioning
confidence: 99%
“…(10). Thus, the computation of the FEC is not dependent on whether Z or R 2 ⊥ is used in determining the self-consistent equation.…”
mentioning
confidence: 99%
“…In concert with theoretical studies (9, 14, 15), these measurements can be used to construct the free energy landscape of proteins and RNA. For example, we have shown that, by using dynamics of nonequilibrium stretching experiments, one can infer the distribution of free energy barriers in the absence of force (16). Measurement of distribution of free energy barriers requires following time-dependent events, at the single molecule level, when unfolding is induced by force.…”
mentioning
confidence: 99%